The Level and Significance of Circulating Angiotensin-III in Patients with Coronary Atherosclerosis - Yao, Guoqing; Li, Wenjing; Liu, Wenzhao; Xing, Jingbo; Zhang, Cheng (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Objective. Angiotensin-III (Ang-III) is the downstream product of angiotensin-II (Ang-II) metabolized by aminopeptidase A (APA). At present, the research of Ang-III mainly concentrates on hypertension and the central renin-angiotensin system (RAS). However, few studies have focused on the relationship between Ang-III and coronary atherosclerosis (CAS). Methods and Results. Plasma Ang-III and APA levels were measured by the enzyme-linked immunosorbent assay (ELISA) in 44 normal subjects and 84 patients confirmed as having CAS by coronary angiography. Circulating Ang-III levels were significantly lower in patients with CAS than in normal controls (P=0.013). APA levels were slightly lower in the CAS group (P=0.324). According to the severity of atherosclerosis, CAS patients were divided into two groups. Compared with the controls, the APA and Ang-III levels were lower in the high scoring group and APA decreased significantly. Conclusions. Circulating Ang-III levels were reduced in patients with CAS, and the possible reason may be related to the decrease in the APA level.